A collaborative excitation method for piezoelectric stick-slip actuator to eliminate rollback and generate precise smooth motion. (1st May 2022) - Yu, Hongpeng; Liu, Yingxiang; Deng, Jie; Zhang, Shijing; Chen, Weishan
Highlights: A method is proposed to improve the motion smoothness of stick–slip actuators. A 2-DOF piezoelectric actuator is fabricated to verify the proposed method. A theoretical model is derived to explain the principle of the proposed method. Experiments are conducted to present the smooth motion and precise tracking. The method shows the long stroke, high precision and strong carrying capability. Abstract: The actuators with the abilities of precise trajectory tracking in large range are widely needed in many applications. However, nearly all the previous achievements can only accomplish the integration of high precision and long stroke in the point-to-point positioning, but not the trajectory tracking. Hence, this work proposes a collaborative excitation method for the stick–slip driving principle to eliminate the rollback and improve the motion smoothness. A 2-DOF piezoelectric actuator is fabricated to verify the validity, and the theoretical models are derived to explain the driving principle. The experimental results indicate that the rollback is eliminated completely, and the motion smoothness is improved significantly. The unlimited motion range and the motion resolution higher than 3.96 nm are presented. The steady load capability is more than 15.6 times of the self-weight. Furthermore, the close-loop trajectory tracking errors are smaller than 0.13 µm, which are less than 18.9% of the conventional excitation method. Besides, the precise planar tracking is also accomplished. To sum up, the proposed method improves the precise tracking performances of the piezoelectric stick–slip actuator significantly, and it has broad applicability on other actuators as well. Hence, it shows great prospects in the applications requiring precise trajectory tracking.